Phytochemical Fortification in Fruit and Vegetable Beverages with Green Technologies - Francisco Artés-Hernández (MDPI AG, 2021)
Background: Phytochemical, bioactive and nutraceutical compounds are terms usually found in the scientific literature related to natural compounds found in plants linked to health-promoting properties. Fruit and vegetable beverages (mainly juice and smoothies) are a convenient strategy to enhance the consumption of horticultural commodities, with the possibility of being fortified with plant byproducts to enhance the content of bioactive compounds. Objective: This review aims to analyse the different green technologies applied in beverage processing with a fortification effect on their health promoting compounds. Results: Fortification can be performed by several strategies, including physical elicitors (e.g., processing technologies), plant/algae extract supplementation, and fermentation with probiotics, among others. Thermal processing technologies are conventionally used to ensure the preservation of food safety with a long shelf life, but this frequently reduces nutritional and sensory quality. However, green non-thermal technologies (e.g., UV, high-pressure processing, pulsed electric fields, ultrasounds, cold plasma, etc.) are being widely investigated in order to reduce costs and make possible more sustainable production processes without affecting the nutritional and sensory quality of beverages. Conclusions: Such green processing technologies may enhance the content of phytochemical compounds through improvement of their extraction/bioaccessibility and/or different biosynthetic reactions that occurred during processing.